Intravenous Infusion of Lidocaine for Bowel Function Recovery After Major Colorectal Surgery: A Critical Appraisal Through Updated Meta-Analysis, Trial Sequential Analysis, Certainty of Evidence, and Meta-Regression - Chen, Po-Chuan; Lai, Chao-Han; Fang, Ching-Ju; Lai, Pei Chun; Huang, Yen Ta (Frontiers in Medicine, 2022)
Background Intravenous infusion of lidocaine (IVF-Lido) during the perioperative period is an option to accelerate bowel function recovery after major colorectal surgery. However, previous meta-analyses have shown inconsistent conclusions. Recent randomized controlled trials (RCTs) have been reported after the publication of a previous meta-analysis. Aim We conducted an updated and comprehensive meta-analysis to determine the effects of IVF-Lido on time to first flatus and defecation after major colorectal surgery. Methods We performed a systematic review according to the Preferred Reporting Items for the Systematic Reviews and Meta-Analysis Protocols 2020 guideline. Only RCTs were included. The revised Cochrane risk-of-bias tool was chosen for appraisal. Meta-analysis with meta-regression and trial sequential analysis was carried out. The Doi plot was presented to evaluate publication bias. The Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) methodology was executed to evaluate the certainty of evidence (CoE). Results Thirteen RCTs with 696 participants were enrolled. IVF-Lido significantly decreased the time to first flatus [mean difference (MD) = −6.03 h; 95% confidence interval (CI): (−8.80, −3.26)] and first defecation [MD = −10.49 h; 95% CI: (−15.58, −5.41)]. Trial sequential analysis yielded identical results and ampleness of required information sizes. No obviousness in publication bias was detected, and the CoE in GRADE was low in both outcomes. Meta-regression showed that a significantly shorter time to the first defecation was associated with studies with more improvement in pain control in comparison of two groups and better-improved analgesia in the control group. Conclusions We discretionarily suggest the use of IVF-Lido on postoperative bowel function recovery following major colorectal surgery. Beyond the analgesic effects, IVF-Lido might have additional benefits when postoperative pain relief has already been achieved. Considering the high heterogeneity in this updated meta-analysis, more RCTs are needed. Systematic Review Registration https://inplasy.com/inplasy-2020-7-0023/, INPLASY [202070023].